(untitled) (American Journal of Islam and Society, 2000)
The author of this book, a graduate in theology and philosophy, gives an unusual and interesting analysis of the conveying of God’s message to humankind and its final conveyor, the Prophet Muhammad. He focuses on the Prophet as a person, and how, like previous prophets, he was chosen by God at an appropriate time. Readers are not taken chronologically through the Prophet’s life; instead, the author examines aspects of the conveying of God’s guidance and, in particular, the relationship between God and His messenger. Examples of situations in the Prophet’s life are carefully compared with similar situations in the lives of earlier prophets that are described in the Qur’an and Islamic traditions, as well as in the traditional writings of the Jews and Christians, such as the Old and New Testaments and the Torah. The result is a rich combination of psychology, philosophy, history, and geography in seven chapters, the first five of which begin with a quotation from the Qur’an, pro viding the main theme of that chapter. Communication between God and Muhammad takes various forms, depending on the circumstances: advice, warning, comfort, or explanation. The verb "speak" can be interpreted in different ways. As revelation, it is reserved for God’s chosen prophets. However, God also "speaks" to the general population ...